Should there be an app for that? Australian perspectives on the utility of a mobile app to support people in the criminal justice system - Taylor, Helen (Probation journal, 2024)
Mobile technology presents opportunities within the justice system to support and promote behaviour change and the past decade has seen increased development and use of mobile applications for this purpose. This article aims to contribute to this burgeoning area by presenting the findings of research which scoped the utility of a mobile application (app) intended to support Indigenous people on bail or parole in the Australian Capital Territory. The project sought the views of 12 people with lived experience of the criminal justice system, as well as 23 professional stakeholders who engage with the justice system, to determine the utility of such an app.